IMPLEMENTATION OF AGROFORESTRY CONCEPT ON OIL PALM PLANTATION: PROSPECTS AND CHALLENGES - Judijanto, Loso (Seven Editora, 2025)
In Indonesia, oil palm plantations are often associated with problems such as deforestation, biodiversity loss, and land conflicts. Agroforestry is a sustainable alternative that combines oil palm plantations with other agricultural or forestry crops to reduce environmental impacts. Most people believe that this idea can increase land productivity, improve ecosystem quality, and provide socio-economic benefits to communities living around it. However, the use of agroforestry in the oil palm industry still faces technical, social, and institutional problems that require further research. The purpose of this study is to examine the prospects and challenges of implementing the agroforestry concept in oil palm plantations in Indonesia. In addition, this study aims to provide an understanding of the potential of agroforestry as an alternative method to achieve more sustainable plantation practices. This research uses a qualitative method with a literature review approach. The data were collected from environmental organization reports, scientific publications, and relevant policy documents. Across various scales of oil palm plantations, the analysis was conducted in a descriptive-critical manner with a focus on success patterns, implementation barriers, and opportunities for agroforestry integration. According to research, agroforestry can increase biodiversity, reduce the risk of soil erosion, and generate additional income for farmers. However, lack of incentives, inconsistent regulations, and lack of knowledge of farmers about proper agroforestry techniques make it still underused. As a sustainability strategy, the application of the agroforestry concept in oil palm plantations has promising prospects. However, to overcome various obstacles to its implementation, policy support, technical training, and collaboration between the government, companies, and communities are needed.DOI: https://doi.org/10.56238/sevened2025.029-008